Relationships Of Knowledge, Attitude, And Behavior, Mother In Provide Asi Food With A Baby Nutrition Status 6-11 Months - Haerani; Hariyanti Haris; Ade Reskiyanti (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2020)
Nutrition improvement efforts aim to improve the nutritional status of the community, prioritizing high-risk community groups, namely infants, toddlers, school-age, adolescents, pregnant and lactating mothers, and the elderly. This study aims to determine the relationship of knowledge, attitudes, and behavior of mothers in supplementary feeding with the nutritional status of infants 6-11 months in the work area of ​​caile district health center. Fur ends in 2019. The research design used in this study was cross-sectional. The population in this study were mothers who had babies aged 6-11 months as many as 359 people in the work area of ​​the caile puskesmas. Kab fur tip. Bulukumba. The sample in this study was 47 people. The sampling technique in this study uses a simple random sampling method that is sampling in a random manner without regard to strata that exist in members of the population. There is a relationship between the mother's knowledge in complementary feeding and the nutritional status of infants with a gloss of p: 0,000. There is a relationship between maternal attitudes in supplementary feeding with the nutritional status of infants with a gloss of p: 0,000. There is a relationship between maternal behavior in supplementary feeding with the nutritional status of infants with a gloss of p: 0,000. There is a relationship between knowledge, attitudes, and behavior of mothers in supplementary feeding with the nutritional status of infants 6-11 months in the working area of ​​caile kec. Fur ends of 2019 with a value of p: 0,000. Further research needs to be carried out on factors that affect nutritional status with a broader scope such.